The Relationship between Body Shaming Treatment and Body Image in Adolescents in Depok - Milla Evelianti; Nita Sukamti; Meila Kusuma Wardana (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2020)
Since March 2015 at the Asian level, the number of cases of bullying that has happened to students in schools has reached 70%. The impact of body shaming will lead to poor self-assessment. This study aims to determine whether there is a relationship between body shaming treatment on body image among adolescents in Depok. The design of this research is quantitative with cross sectional approach. The sample in this study is 81 students in Depok. The sampling technique used is cluster random sampling. Data are analyzed using Chi-Square test. The results showed that there is a relationship between body shaming treatment on body image among adolescents in the Depok area, aimed at p values ​​of 0.017 (p <0.05). Teenagers who get a low body shaming treatment will have a positive body image and vice versa. Intervention needs to be done to reduce body shaming treatment in adolescents in improving body image.